"I actually finally feel like the cigarettes aren't controlling me." – Interviews with participants smoking very low nicotine content cigarettes during a residential study. (1st February 2021) - Denlinger-Apte, Rachel L.; White, Cassidy M.; Donny, Eric C.; Hatsukami, Dorothy K.; Benowitz, Neal L.; Carpenter, Matthew J.; Smith, Tracy T.
Highlights: In-depth interviews were conducted with participants (N = 16) enrolled in a residential smoking study of very low nicotine content (VLNC) cigarettes. Some participants expected to compensate for the reduced nicotine levels by smoking more cigarettes; however, they were surprised when they did not increase their smoking during the study. A subset of participants reported experiencing minor withdrawal symptoms after exclusively smoking VLNC cigarettes. Some participants reported feeling less dependent after exclusively smoking VLNC cigarettes while others thought VLNC cigarettes could help people quit smoking. Abstract: Background: The U.S. Food and Drug Administration (FDA) is considering a low-nicotine product standard for cigarettes. The purpose of this qualitative study was to explore participants' experiences after 72 hours of exclusively smoking very low nicotine content (VLNC) cigarettes. Methods: We conducted a residential study during which participants who smoked cigarettes (N = 16) stayed in a smoking-friendly hotel for 5 days/4 nights. Participants only had access to VLNC cigarettes and were told the cigarettes had 97% less nicotine compared to conventional cigarettes. We conducted individual interviews with participants to assess their initial expectations about VLNC cigarettes, subjective experiences when smoking VLNC cigarettes, opinions regarding a low-nicotine product standard, and predicted use behavior if only VLNC cigarettes were available. Interviews were transcribed verbatim and analyzed using thematic analysis methods. Results: Several participants expected, prior to trying VLNC cigarettes, to compensate for the reduced nicotine levels by smoking more cigarettes but were surprised when they did not increase their smoking. A subset of participants reported experiencing minor withdrawal symptoms, such as irritability and fatigue. Several participants reported feeling less dependent after exclusively smoking VLNC cigarettes. Most participants said they would smoke VLNC cigarettes if they were the only cigarettes available to purchase. Some also said that smoking VLNC cigarettes could help people taper down or quit smoking. Conclusions: Health communication strategies are needed to inform people who smoke about what to expect from a low-nicotine product standard for cigarettes in order to maximize the public health impact of the policy and increase support.